2020
DOI: 10.21203/rs.3.rs-96702/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charge-Transfer Regulated Visible Light Driven Photocatalytic H2 Production and CO2 Reduction in Tetrathiafulvalene Based Coordination Polymer Gel

Abstract: The much-needed renewable alternatives to fossil fuel can be achieved efficiently and sustainably by converting solar energy to solar fuels via hydrogen generation from water or CO2 reduction. In this regard, a soft processable metal-organic hybrid semiconducting material has been developed and studied for photocatalytic activity towards H2 production and CO2 reduction to CO and CH4 under visible light and direct sunlight irradiation. A tetrapodal low molecular weight gelator is synthesized by integrating tetr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…60 In addition, the characteristic vibration of CO* intermediates displayed a weak peak at 2065 cm −1 . It was considered that the small amount of CO* generated in CO 2 PR was readily converted into CH 3 O* and CHO* intermediates to form CH 4 rather than desorbing from PMo 12 @NiCo-LDH and generating CO, 61…”
Section: Insights Into the Photocatalytic Mechanism Of Co 2 Prmentioning
confidence: 99%
“…60 In addition, the characteristic vibration of CO* intermediates displayed a weak peak at 2065 cm −1 . It was considered that the small amount of CO* generated in CO 2 PR was readily converted into CH 3 O* and CHO* intermediates to form CH 4 rather than desorbing from PMo 12 @NiCo-LDH and generating CO, 61…”
Section: Insights Into the Photocatalytic Mechanism Of Co 2 Prmentioning
confidence: 99%
“…36−38 In this context, only a handful of literature is available for CO 2 reduction into fuels and value-added chemicals based on metal−organic gel catalysts; for example, Maji and co-workers reported zinc-and ruthenium-mediated metal−organic gel-based photocatalysts for CO 2 reduction into CO and CH 4 . 22,24 Lan and co-workers reported a copperhydrogel-derived catalyst for CO 2 conversion into C 2 H 4 and CH 4 . 39 Su et al reported an iron−sulfur cluster-containing hydrogel for CO 2 reduction into formate.…”
Section: ■ Introductionmentioning
confidence: 99%